2003
DOI: 10.1248/bpb.26.462
|View full text |Cite
|
Sign up to set email alerts
|

Scropolioside-D2 and Harpagoside-B: Two New Iridoid Glycosides from Scrophularia deserti and Their Antidiabetic and Antiinflammatory Activity.

Abstract: Five iridoid glycosides, including the two new compounds scropolioside-D(2) (1) and harpagoside-B (2), were isolated from the aerial parts of Scrophularia deserti DEL (Scrophulariaceae). Their structures were elucidated on the basis of spectral data to be 6-O-[2",4"-di-O-acetyl-3"-O-trans-cinnamoyl)-alpha-L-rhamnopyranosyl]-8 alpha-hydroxymethyl-1 alpha,5 beta,6 alpha,7 alpha,9 beta-pentahydro-7(8)-epoxy-2-oxaind-3-ene-1-O-beta-D-glucopyranoside-6'-O-acetate (1) and 5-O-beta-hydroxy-8-O-beta-trans-cinnamoyl-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 14 publications
1
45
0
2
Order By: Relevance
“…A wide range of medicinal properties are attributed to Verbascum species (Vijayavitthal et al, 1998;Tuzlaci and Erol, 1999;Konoshima et al, 2000;Sezik et al, 2001;Stevenson et al, 2002;Turker and Camper, 2002;Ahmed et al, 2003;Senatore et al, 2007;Amirnia et al, 2011;Karamian and Ghasemlou, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of medicinal properties are attributed to Verbascum species (Vijayavitthal et al, 1998;Tuzlaci and Erol, 1999;Konoshima et al, 2000;Sezik et al, 2001;Stevenson et al, 2002;Turker and Camper, 2002;Ahmed et al, 2003;Senatore et al, 2007;Amirnia et al, 2011;Karamian and Ghasemlou, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…In another similar study, intraperitoneal treatment with 20 mg/kg of harpagoside ameliorated the development of zymosan-induced arthritis and reduced pathological changes in joints of mice [29] . Paw swelling in mice also reduced by oral administration of harpagoside (10 mg/kg) isolated from the aerial parts of Scrophularia deserti [30] . There is moderate evidence for daily intake of 60 mg harpagoside in the treatment of spin, knee, and hip osteoarthritis [31] .…”
Section: Evidences For Anti-inflammatory Activity Of Harpagosidementioning
confidence: 99%
“…The test compounds produced a significant inhibition of inflammation after 3 h. However, the dose dependent effect of the compounds could not be studied due to paucity of the compounds. Some other iridoid glucosides from the genus Scrophularia (Scrophulariaceae) have also been reported to possess anti-inflammatory activity [11], wherein the compounds containing cinnamoyl moiety at C-8 exhibited a potent activity in the range 20 to 30% at a dose of 10 mg/kg [12]. It may, therefore, be concluded that methyl group at position-8, as in the case of compound 2 (28.6%), may also play a significant role in displaying a good antiinflammatory activity.…”
Section: Part B: Anti-inflammatory Activitymentioning
confidence: 99%